Pengaruh Penggunaan E-Wallet dan Literasi Keuangan Terhadap Perilaku Pembelian Impulsif - Tri Nanda Aulia; Edy Suryadi; Heni Safitri (Politeknik Ganesha Medan, 2023)
The purpose of this study is to determine the impact that using e-wallets and financial literacy has on impulsive buying behaviour. An associative research is a type of research. Purposive samples of a total of 215 respondents have been chosen for the sample selection in this study. The analysis used is the classical assumption test, multiple linear regression analysis, multiple correlation coefficients, coefficient of determination, and partial effect test (t test). The classical assumption test has shown that the data are normally distributed, linear in shape and have no multicolinearity problems. A multiple correlation coefficient indicates that an R test has been performed with a value of 0.970. This implies that a very strong correlation of 0.970, which is the sum of ewallet use and Financial Literacy for impulse shopping behavior has been observed. he results of the coefficient of determination (R2) obtained a value of 0.970 or 97% meaning that impulsive buying behavior is influenced by e-wallet use and financial literacy, while 3% impulsive buying behavior is influenced by other variables not examined in this research. The partial test showed that a variable use of e-wallet has a positive and significant impact on impulsive buying behaviour, but the financial literacy factor had a negative and significant influence on impulsive buying behavior.